Kontakty prawnicze między Uniwersytetem Jagiellońskim i Uniwersytetem Wrocławskim w latach 1811–1914 - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Legal contacts between the Jagiellonian University and University of Wrocław in 1811–1914 were not very frequent. They involved mainly people who graduated in law from the Jagiellonian University and came to Wrocław to pursue further studies. Most of them were future professors of the Jagiellonian University. This occurred primarily in the first half of the 19th century, during the popularity of the historical school in the German study of law and of Hegel’s views, which made the University of Wrocław rather attractive. An important role in these contacts was played by Jerzy Samuel Bandtkie’s patronage in Kraków and Carl August Dominik Unterholzner’s patronage in Wrocław. In the first half of the 19th century these were both personal and scholarly contacts, in the second — mainly scholarly contacts. Contacts that went in the opposite direction, from Wrocław to Kraków, were limited largely to Józefat Zielonacki, a professor at both universities.
Keywords: Uniwersytet Jagielloński; Uniwersytet Wrocławski